Integrating BDI and Bayesian Networks in Agent Reasoning - Boff, Elisa; Vicari, Rosa Maria; Fagundes, Moser S. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2009: Anais do VII Encontro Nacional de Inteligência Artificial, 2009)
This paper focuses on a Social Agent which has been modeled using probabilistic networks and acts in an educational application. Using the Social Agent as a testbed, we present a way to perform the deliberation process in BDI (Belief-Desire-Intention) and Bayesian networks. The assemblage of mental states and Bayesian Networks is done by viewing beliefs as networks, and desires and intentions as particular chance variable states that agents pursue. In this work, we are particularly concerned with the deliberation about which states of affairs the agent will intend. The focus of this paper is on how to build a real application by using the deliberation process developed in one of our previous work.